Variety Development Cost versus Variety Adoption in Major Cereals in Nepal - Shrestha, Hari K; Manandhar, Hira K; Regmi, Punya P (Nepal Journal of Science and Technology, 2013)
This study was carried out to measure the research investment in major cereals, namely, rice, maize and wheat, and identify the general adoption status of their released varieties in Nepal. Financial resource use was derived from disaggregated expenditure whereas human resource use was approximated from full time equivalent (FTE) of researchers in each crop through questionnaire survey. Information regarding the farmers’ adoption was collected through group interaction with extension staff in selected hill and Terai districts from each of five geographical regions of the country. The variety development cost was Rs. 38.1 million in maize, 15.8 million in wheat, and 14.6 million in rice during 2001-2010 at 2000/01price. Of the total FTE researchers, 35 in rice, 28 in wheat and 18 in maize were involved in various disciplines of the crop research whereas 8 FTE researchers were involved in breeding of each of the crops. Among the most common rice varieties, Khumal-4 was adopted in 55% area in Kavre district, Radha-12 was adopted in 40% area in Sunsari district and Radha-4 was adopted in 70% area in Banke district in the main season. Indian hybrid maize was common in most of the Terai districts with maximum adoption in 95% area in Bara district. Among the popular wheat varieties, Gautam was common in hill and Terai districts with the adoption range from 30 to 50% of total wheat area. Compared with maize and wheat, adoption of improved rice varieties was relatively low since high yielding and suitable rice varieties were still lacking for various domains. Nepal Journal of Science and Technology Vol. 13, No. 1 (2012) 7-15 DOI: http://dx.doi.org/10.3126/njst.v13i1.7393